Strengthening EU Cyber Resilience: A Critical Analysis of the Cyber Solidarity Act’s Legislative Framework - Dewi , Arie Setya; Nugrahani, Henny Saptatia Drajati (Journal of Islamic World and Politics, 2024)
This study aims to analyze the importance of the EU’s Bill on Cyber Solidarity Act (bill) in order to strengthen the EU’s cyber resilience by enhancing preparedness and achieving equal capacities of EU member states in dealing with significant and large-scale cyber incidents. The cross-border nature of cybersecurity incidents can be too disruptive for a single or some affected member states to tackle on its own, necessitating collective action at the EU level. This study applied the qualitative method with library research using secondary data sourced from scientific journals and official documents. The authors used English school theory through the lens of the concept of solidarity. The result of this study reveals the important role of the bill in the EU in reinforcing cooperation among member states and EU institutions, thereby making the region fully prepared and more responsive to cybersecurity incidents. The main finding of this study is that the bill will become a legal umbrella for both member states and EU institutions to be able to implement the pre-incident, during-incident, and post-incident actions in a more coordinated manner thus, it will enhance the EU's overall capacities to deal with cybersecurity incidents.